Methods and feasibility of conducting pragmatic clinical trials in small animal first opinion practice. - Doit, Hannah (2023)
Chronic kidney disease (CKD) is an important cause of morbidity and mortality in cats, for which many research uncertainties remain unanswered. As for much of veterinary healthcare, the evidence base for treatment decision-making is limited. For the small number of research questions where randomised controlled trials (RCTs) are published, sample sizes are small, and the external validity of results can be limited because the patients included are not representative of the wider population who may have comorbidities. In addition, existing published research evidence does not always address outcomes of importance to treatment decision makers.